The Relation among Prostate Cancer Knowledge and Psychosocial Factors for Prostate Cancer Screening among African American Men: a Correlational Study - Sabrina L. Dickey; Aurellia Whitmore; Ellen Campbell (AIMS Press, 2017)
African American (AA) men face disproportionately higher rates of prostate cancer (PCa) in comparison to other races. In addition, higher mortality rates from PCa amongst AA men signifies PCa as a formidable health disparity. Inconsistent PCa screening guidelines among medical organizations, further clouds one's decision on receiving a PCa screening. Examining various relations among factors which influence PCa screening may provide insight into their decision whether or not to receive a PCa screening. The purpose of the study was to examine the presence of associations among PCa knowledge, psychosocial factors, and PCa screening over a six month time frame. There were 76 participants at baseline, intervention group (n = 37) and control group (n = 35) and 54 participants, intervention group (n = 26) and control group (n = 28) remained at the 6 month follow up. At the six month follow up, the control group was more likely to have not received a PCa screening and the intervention group was more likely to have received a PCa screening, p < 0.01. PCa knowledge scores rose from 49% to 71%, intervention group, and 52% to 58%, control group. Significant associations were found among the following covariates, age and religion (rs = 0.499, p < 0.01), income and education (rs = 0.535, p < 0.01), income and healthcare coverage (rs = 0.528, p < 0.01), income and PCa knowledge at 6 months (rs = 0.424, p < 0.01), PCa screening and religion (rs = 0.353, p < 0.01), healthcare empowerment and preparation for decision making (rs = 0.421, p < 0.01), decisional self-efficacy and active surveillance knowledge (rs = 0.377, p < 0.01), and active surveillance knowledge and PCa knowledge (rs = 0.497, p < 0.01). The study revealed associations among PCa knowledge and psychosocial factors regarding a decision for PCa screening among the PCa high risk group, AA men.